2019
DOI: 10.1007/s13205-019-1804-7
|View full text |Cite
|
Sign up to set email alerts
|

The concurrent effects of azurin and Mammaglobin-A genes in inhibition of breast cancer progression and immune system stimulation in cancerous BALB/c mice

Abstract: In the present study, the simultaneous application of azurin gene of P. aeruginosa and MAM-A antigen on the induction of immune responses against breast cancer tumors was investigated in BALB/c mice. The pBudCE4.1-azurin-MAM-A recombinant vector was generated and prepared at a large scale. This recombinant vector alone or combined with chitosan nanoparticles was infused into the hip muscle of animals. Animals were divided into the "prevention" and "therapy" categories. The animals of prevention category were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…High toxicity is critical in producing anticancer drugs; although toxicity results in this research were satisfying, it takes much effort to put these valuable results into use at clinical levels. Encapsulating Az with CS can protect it from the attack of the immune system and can help to pass through main drug-resistant mechanisms [1,45,46] ; in addition, it helps Az to remain in the targeted areas longer than free protein and extends drug releasing time. One of the problems we face in common cancer treatments is that in treatments like chemotherapy, there is no border in attacking healthy and cancerous cells, but by using nanocarriers, we can reduce the harmful attacks on healthy cells.…”
Section: Discussionmentioning
confidence: 99%
“…High toxicity is critical in producing anticancer drugs; although toxicity results in this research were satisfying, it takes much effort to put these valuable results into use at clinical levels. Encapsulating Az with CS can protect it from the attack of the immune system and can help to pass through main drug-resistant mechanisms [1,45,46] ; in addition, it helps Az to remain in the targeted areas longer than free protein and extends drug releasing time. One of the problems we face in common cancer treatments is that in treatments like chemotherapy, there is no border in attacking healthy and cancerous cells, but by using nanocarriers, we can reduce the harmful attacks on healthy cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mammaglobin is a well-known specific marker for breast cancer, and the high expression of mammaglobin is associated with tumour stage, 9 histological grading, 3,6 lymph node metastasis, 3,19 and endocrine state. 5,6 In this study, we found mammaglobin expression to be significantly associated with lymph node status, histopathological grade, and Ki-67 expression, despite its low sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Mammaglobin is a well-known specific marker for breast cancer, and the high expression of mammaglobin is associated with tumour stage, 9 histological grading, 3,6 lymph node metastasis, 3,19 and endocrine state. 5,6 In this study, we found mammaglobin expression to be significantly associated with lymph node status, histopathological grade, and Ki-67 expression, despite its low sensitivity. These findings agree with those reported by previous studies, in which mammaglobin overexpression was found to be correlated with lymph node metastasis and was identified as a potential protein metastasis marker in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Azurin has attracted much attention in the last two decades, because it preferentially enters into many human cancer cells and induce apoptosis [8,[13][14][15]. This protein and its derived peptide p28 have anticancer activity that has been confirmed in mouse-based tumor models and various cancer cells [16,17].…”
Section: Introductionmentioning
confidence: 99%